Education, political empowerment and Muslim women in the Middle East – Understanding the paradox - Amriah Buang; Ratnawati Yuni Suryandari (Faculty of Social Sciences and Humanities, UKM,Bangi, 2011)
Article 3 of the United Nations’ Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) requires that state parties take all appropriate measures, including legislation, to guarantee women the exercise and enjoyment of human rights and fundamental freedoms on a basis of equality with men in all fields of life. The mainstream image of Islam seems to have been one that apparently portrays Islam and its stipulations on women as anathema to those of CEDAW. Curiously, the direct relationship between orthodox Islam or Muslim societies with perceived mistreatment or disempowerment of women does not materialise as clearly or forthrightly as anticipated. This paper demonstrates that recent CEDAW examinations reveal that educational attainment of Muslim women in orthodox Muslim countries in seven orthodox Muslim countries in the Middle East, namely, Saudi Arabia, United Arab Emirates, Qatar, Bahrain, Oman, Kuwait and Iran has vastly improved especially with respect to higher education. Yet, the facts also reveal that high education does not generally translate into greater political empowerment of the women. This paper then seeks to understand this apparent paradox with special reference to the Saudi Arabian case. It reasons that orthodox, conservative and negative perspectives and stereotypes of women in Islam are but only part of the answer. The other part would be that the educated Muslim women in orthodox Muslim countries of the Middle East as elsewhere do weigh things together in deciding which careers to pursue; that they deliberately decide in favour of the education and health profession because these are considered religiously more doable than politics and governance. The mainstream Western notions that rather simplistically equate educational with political empowerment does not happen the way it is expected for the Muslim women because of these non-secular considerations that engage them but that were not factored in and recognised in the conventional notions.